California Advocate Newspaper's Drum Major for Justice Dinner at Hilton Hotel - Watkins, Howard::::::::: (1988)
Mark Kimber, Pauline Kimber, Parren Mitchell, Les Kimber, Bill Riddlesprigger; in back: Rev. Chester Riggins